A preliminary study of e-learning critical success factors: the student perspectives / Othman Zainon, Maslin Masrom and Rosdiana Rahiman - Zainon, Othman (Penerbit UiTM (UiTM Press), 2009)
In this recent day, information technology becomes prominent to support teaching and learning activities. E-learning also known as online learning was one of information technology (IT) tools introduced at College of Science and Technology (CST), University Technology Malaysia (UTM) City Campus Kuala Lumpur since 2001. It represents an innovative shift in the field of learning, providing rapid access to specific knowledge and information, and offers online instruction that can be delivered anytime and anywhere through a wide range of electronic learning solutions such as Webbased courseware and online discussion groups. It can be viewed as making learning materials such as presentation slides available on the web. The aim of e-learning, as any other learning approach is to achieve the learning objectives. Until today students in CST used the e-learning technology only for accessing the syllabus and course content, submitting assignments and taking class quizzes.